2017
DOI: 10.3171/2017.1.focus16520
|View full text |Cite|
|
Sign up to set email alerts
|

Application of emerging technologies to improve access to ischemic stroke care

Abstract: During the past 20 years, the traditional supportive treatment for stroke has been radically transformed by advances in catheter technologies and a cohort of prominent randomized controlled trials that unequivocally demonstrated significant improvement in stroke outcomes with timely endovascular intervention. However, substantial limitations to treatment remain, among the most important being timely access to care. Nonetheless, stroke care has continued its evolution by incorporating technological adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…In neurosurgery, robotic assistance has been used for epilepsy evaluation,5 subcortical surgery6 and spine surgery 7. We identified only one report of a robotic system used for cerebral angiography, in which Vuong and colleagues8 describe the use of the Magellan Robotic Catheter System (Hansen Medical, Mountain View, California, USA), but no intervention was performed nor was the system adapted to microcatheter and microwire manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…In neurosurgery, robotic assistance has been used for epilepsy evaluation,5 subcortical surgery6 and spine surgery 7. We identified only one report of a robotic system used for cerebral angiography, in which Vuong and colleagues8 describe the use of the Magellan Robotic Catheter System (Hansen Medical, Mountain View, California, USA), but no intervention was performed nor was the system adapted to microcatheter and microwire manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, it was the factors that impact during prehospital time, here defined as the onset time, that were studied. Prehospital time was found to be only linked to prehospital transport, optimized by mobile stroke treatment units, or telemedicine or robotically assisted angiography, (Vuong et al, 2017) although few factors were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a series of magnetic resonance imaging (MRI) studies that estimate stroke onset time (Berthet et al, 2014;Jokivarsi et al, 2010;McGarry et al, 2017). However, with the exception of prehospital transport (Vuong et al, 2017), little has been reported about the onset time factors that affect prognosis and there is no evidence as to which relative factors of illness may have an impact on stroke onset time. As patients who experience stroke symptoms, and have knowledge of them, may be more motivated to attend hospital, this study focuses on such patients and any associated illness.…”
Section: Introductionmentioning
confidence: 99%
“…19 There are several emerging technologies such as telemedicine and mobile stroke treatment units that are being used to help address these disparities. 20 Studies have demonstrated that telemedicine in a stroke system of care plays a fundamental role in increasing the use of thrombolysis, bridging the geographical gaps in underserved areas, facilitating an accurate triage of stroke patients to the appropriate providers, and allowing rapid visualization and interpretation of neuroradiologic data. [52][53][54][55] However, in several states, Medicaid does not currently reimburse the provider for stroke telemedicine, 21 although, starting in 2021, Medicare will reimburse regardless of where the patient receives treatment.…”
mentioning
confidence: 99%